Single Enantiomer Versus Racemate: Chiral Distinction in the Proton Pump Inhibitors Omeprazole and Esomeprazole. Issue 4 (12th March 2014) - Marom, Hili; Pogodin, Sergey; Agranat, Israel
ABSTRACT Chiral distinction in the proton pump inhibitor drugs omeprazole and in its chiral‐switch esomeprazole magnesium was studied employing the Density Functional Theory (DFT) method. At B3LYP/6‐311G(d, p), the 6‐methoxy∙∙∙6‐methoxy and 5‐methoxy∙∙∙5‐methoxy homochiral and heterochiral dimers were calculated. The chiral distinction free energies (ΔΔG298, (RS‐SS)) between the cyclic C2‐(S, S)‐ and Ci‐(R, S)‐dimers with two intermolecular hydrogen bonds are 3.8, 1.9 (with BSSE counterpoise correction), and –6.9 (with D3 dispersion and BSSE counterpoise corrections) kJ/mol. Adding water as an implicit solvent (polarized continuum model [PCM] model) resulted in a chiral distinction energy of –3.3 kJ/mol, indicating a reversal of the order of the relative stabilities of C2‐(S, S)‐ and Ci‐(R, S)‐dimers. The chiral distinction free energies between the corresponding (less stable) C1‐dimers with one intermolecular hydrogen bond are –9.3, –5.8 (with BSSE CC), 17.6 (D3 + BSSE CC), and –3.2 (H2O) kJ/mol. The results highlight the contention that omeprazole is not just a superposition of its enantiomer constituents. They are consistent with the pharmacological evidence of enantiomer–enantiomer interactions in omeprazole versus esomeprazole and the differences between the drugs omeprazole and esomeprazole magnesium and support the lodged application for regulatory supplementary protection certificate (SPC) exclusivity for the esomeprazole‐related combination drug Vimovo. Chirality 26:214–227, 2014. © 2014 Wiley Periodicals, Inc.